Analysis of Peak Flood Discharge in Small-Scale River Flow Area - Idhar Sahdar; Dede Rohmat; Wati A. Pranoto (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: Flood discharge is a critical component in reducing the impact of flooding in a given location. An analytical technique based on a watershed's morphometric properties is a method for those without a gauge, particularly in small-scale watersheds. Design/methodology/approach: The synthetic unit hydrograph (HSS) approach is used in this study to analyze flood output. This study was conducted in the Akelaka watershed, a sub-watershed of Tayawi. This analysis relies on spatial and attributes data. A spatial study of watershed morphometric properties was obtained by integrating digital elevation model (DEM) data into geographic information system-based applications (GIS). Meanwhile, using rainfall data from 2019 to 2021, a statistical approach is used to calculate the design rainfall intensity, which is then used as an input variable in the HSS analysis. Findings: The findings of hydrographic analysis using Nakayasu HSS demonstrate that the peak flood time (Tp) is 2.8 hours with a maximum flood discharge (Qp) of 56.636 m3/s, 76, 987 m3/s, 88,091 m3/s, and 101,279 m3/s for return periods of two years, five years, ten years, and 25 years. Paper type: Research paper